Turning Feminist Judgments into Jurisprudence: the Women’s Court of Canada on Substantive Equality - Réaume, Denise (Oñati Socio-Legal Series, 2018)
The Women’s Court of Canada project is unique in having chosen to focus its rewriting efforts in a specific area of law - constitutional equality cases. This strategy permits an assessment of the WCC jurisprudence to see if it yields a competing ‘theory’ of equality rights that might be used to systematically critique the real jurisprudence and perhaps produce lines of argument capable of redirecting the real law. This effort reveals the pervasive importance of attention to and representation of context to bringing to life the abstract commitments of an account of substantive equality. While not a new discovery, this demonstration of the work context can do across an array of linked cases is illuminating.